To restrict or not to restrict personal internet usage on the job - Messarra, Leila Canaan (2015)
Purpose – The subject of cyber‐slacking has prompted many organizations to respond by enforcing or implementing policies that restrict internet access. The purpose of this paper is to empirically examine the impact of four internet monitoring policies on cyber‐slacking and work satisfaction. Design/methodology/approach – Employees working in medium‐size organizations in Lebanon were surveyed. Chi‐square tests, correlation, ANOVA, and regression analysis were used to test the hypothesis. Findings – Results indicated that having a free internet access had a positive relation with cyber‐slacking, leading to an increase in work satisfaction. The survey also indicated relationship with demographic factors. Research limitations/implications – Although the research provides useful insight on cyber‐slacking and monitoring policies, it is nevertheless restricted to Lebanese companies. Originality/value – This paper adds to the literature on cyber‐slacking by empirically testing the effect of different monitoring policies.